The Role of Financial Management in Optimizing Company’s Financial Performance - Yayuk Karliena; Suheri Suheri; Mas Findi Mulya Saputra; Fadjar Muliawan (Journal of Social Research, 2026)
Financial management is a key factor in determining the quality of a company's financial performance amidst increasingly complex business competition dynamics. This study aims to analyze the role of financial management in optimizing a company's financial performance through planning, cost control, investment management, risk management, and financial transparency. The study uses a qualitative approach with a descriptive method based on literature studies from various scientific sources and empirical reports. The results show that companies that implement financial management systematically are able to improve operational efficiency, maintain cash flow stability, and increase profitability and company value. Furthermore, financial transparency and accountability have been proven to strengthen investor confidence and expand access to funding. The discussion emphasizes that integration between financial management functions is a determining factor in creating optimal and sustainable financial performance. In conclusion, effective and integrated financial management plays a strategic role in improving a company's financial performance, so it needs to be implemented consistently and adaptively to changes in the business environment.